2009
DOI: 10.1007/s00449-009-0403-0
|View full text |Cite
|
Sign up to set email alerts
|

Production and properties of xylanases from Aspergillus terricola Marchal and Aspergillus ochraceus and their use in cellulose pulp bleaching

Abstract: Aspergillus terricola and Aspergillus ochraceus, isolated from Brazilian soil, were cultivated in Vogel and Adams media supplemented with 20 different carbon sources, at 30 degrees C, under static conditions, for 120 and 144 h, respectively. High levels of cellulase-free xylanase were produced in birchwood or oat spelt xylan-media. Wheat bran was the most favorable agricultural residue for xylanase production. Maximum activity was obtained at 60 degrees C and pH 6.5 for A. terricola, and 65 degrees C and pH 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 32 publications
3
20
0
2
Order By: Relevance
“…As incubation time further increased, the production of xylanase decreased gradually. Our results are concordant to previously study where Aspergillus niger produced maximumxylanase after 72 h of fermentation [10] while, Aspergillus ochraceus produced maximum enzyme after 144 h [13].…”
Section: Optimization Of Incubation Period On Enzyme Productionsupporting
confidence: 83%
“…As incubation time further increased, the production of xylanase decreased gradually. Our results are concordant to previously study where Aspergillus niger produced maximumxylanase after 72 h of fermentation [10] while, Aspergillus ochraceus produced maximum enzyme after 144 h [13].…”
Section: Optimization Of Incubation Period On Enzyme Productionsupporting
confidence: 83%
“…Maximum xylanolytic activities were comparable with those reported for other species of industrial importance with the same substrates: xylanolytic activities produced on corncobs were slightly lower than those reported for A. niger SS7 (Bakri et al, 2008), but considerably higher than those reported for A. terricola, A. ochraceus (Michelin et al, 2010) and A. flavus (de Souza, 1999) on the same carbon source. Activities obtained on wheat bran also resulted higher than the production reported for A. niger SS7 (Bakri et al, 2008) and A. flavus (de Souza, 1999) in this carbon source.…”
Section: Resultssupporting
confidence: 78%
“…A comparison among the results of this study and those using other xylanases is difficult, due to differences in the origin and characteristics of the pulp, differences in pulp pretreatment, different processing conditions, and also due to enzyme characteristics. The reduction obtained in the treatments with P. janczewskii xylanases was higher than to those obtained with some other fungal xylanases, which normally present reductions between 0.9 and 4.6 units in kappa number Madlala et al 2001;Maximo et al 1998;Medeiros et al 2007;Michelin et al 2010;Nair et al 2010;Peixoto-Nogueira et al 2009;Taneja et al 2002). Only one study reported greater reduction, i.e., 10.0, treating a cellulose pulp with A. niger xylanases (Raghukumar et al 2004).…”
Section: Biobleachingmentioning
confidence: 96%